2002
DOI: 10.1080/14639230110119234
|View full text |Cite
|
Sign up to set email alerts
|

Quality of data on subsequent events in a routine Medical Birth Register

Abstract: Changes in question formats may change the quality of register data significantly. Check-boxes seem to improve quality compared to open-ended questions. The data on reproductive history and previous Caesarean sections could be combined routinely to improve the quality of the MBR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
156
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 160 publications
(158 citation statements)
references
References 5 publications
2
156
0
Order By: Relevance
“…A strength of this study is the reliability of the National Medical Birth Register, as shown in previous data quality studies [14,15]. The completeness of the register data allowed us to use accurate exclusion criteria; infants with congenital anomalies, low birth weight, multiple births and births occurring outside the hospital.…”
Section: Commentmentioning
confidence: 88%
“…A strength of this study is the reliability of the National Medical Birth Register, as shown in previous data quality studies [14,15]. The completeness of the register data allowed us to use accurate exclusion criteria; infants with congenital anomalies, low birth weight, multiple births and births occurring outside the hospital.…”
Section: Commentmentioning
confidence: 88%
“…The MBR is a high-quality register coveringmorethan99.9%ofallbirths. 29,31 The data quality, completeness, and accuracy of the HDR have been varied from satisfactory to very good in a systematic review. 28 Infants were followed to the age of 7 years, by which time the diagnosis of CP is generally made.…”
Section: Discussionmentioning
confidence: 99%
“…The data gathered from the mandatory national MBR were supplemented with information gathered from two other mandatory national health registries: HDR and CMR. The unique identification number of each woman enabled robust cross-linking between the three registries, which are considered to have excellent coverage and quality, [25][26][27] and the unique dataset enabled a much more rigorous analysis of associations of demographic factors, such as maternal age, parity and SES, with FOC than was possible in smaller scale studies. 2,7,10,13 A limitation is that SES was undefined for one of four women (25.1%, n = 197 785), which may be a result of the inclusion of young mothers and high proportions of students and stay-at-home mothers.…”
Section: Strengths and Limitationsmentioning
confidence: 99%